2007
DOI: 10.1075/hcp.18.23gor
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of first and second language morphological processing

Abstract: . As many research paradigms dealing with human language, the study of linguistic processing is guided by two important considerations: how authentic and natural the collected speech data are, and therefore, how truly they represent the actual linguistic behavior, and which kinds of instrumental and statistical analyses can be performed on such data. And as in other domains, there is often a conflict between the two considerations, notably, the more authentic the data, say, a long segment of naturally produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It was formulated based on a series of studies comparing real and nonce verb generation by L1 and L2 speakers of Russian. These studies demonstrated a lack of categorical distinction between regular and irregular morphological processing for Russian, either as an L1 or L2 (Gor, 2003, 2004, 2007; Gor & Chernigovskaya, 2001, 2005). Instead, first, the Russian data highlighted the role of two factors in L1 and L2 morphological processing: (a) morphological complexity, or the degree and predictability of the allomorphy, and (b) type frequency, or the frequency of a declensional pattern (i.e., the size of a class of words with the same declensional paradigm).…”
Section: First and Second Language Processing Of Inflectional Morphologymentioning
confidence: 99%
“…It was formulated based on a series of studies comparing real and nonce verb generation by L1 and L2 speakers of Russian. These studies demonstrated a lack of categorical distinction between regular and irregular morphological processing for Russian, either as an L1 or L2 (Gor, 2003, 2004, 2007; Gor & Chernigovskaya, 2001, 2005). Instead, first, the Russian data highlighted the role of two factors in L1 and L2 morphological processing: (a) morphological complexity, or the degree and predictability of the allomorphy, and (b) type frequency, or the frequency of a declensional pattern (i.e., the size of a class of words with the same declensional paradigm).…”
Section: First and Second Language Processing Of Inflectional Morphologymentioning
confidence: 99%
“…For English and Dutch, the regular past tense inflection is more frequent than the irregular ones. The combination verb+regular inflection -ed in English is more likely to be applied to new lexical items (e.g., blog-blogged ; see Gor, 2007) than an irregular verb inflection. Similarly, in Dutch, new lexical verbs generally take the suffix de or te, rather than take an irregular inflection.…”
Section: Introductionmentioning
confidence: 99%
“…This vacillation is attested in dictionaries (e.g., Ožegov andŠvedova 2005, Zaliznjak 2003), and has been studied from a number of theoretical and empirical perspectives (cf. e.g., Andersen 1980;Comrie, Stone andPolinsky 1996, Gagarina 2003;Gor 2007;Gor andChernigovskaya 2004 andGorbačevič 1978, Graudina et al 2001, Janda, Nesset and Baayen 2010Kiebzak-Mandera et al 1997;Krysin 1974;Nesset 2008Nesset , 2010aNesset and Janda 2010;Svistunova 2008; Tkachenko and Chernigovskaya 2010 and references therein). However, there is also a diachronic side to sufix shift.…”
Section: Overviewmentioning
confidence: 99%